Concentration Effect of Brotowali Stem (Tinospora Crispa (L.)) in Ethanol Extracts on the Α-Glukosidase Enzyme Inhibition (Indonesian Journal of Chemical Science, 2022)
Antidiabetic oral use in the long run will have an effect on the body, thus providing a need for such medications as herbal plants. Brotowali plants are effective in treating diseases such as diabetes because they contain active borapetoxide c and borappentol B compounds. The purpose of the study is to identify the effect of inhibitor activity α - glucosidase against inhibition of the enzyme α - glucosidase using variations in the concentration of ethanol extract of brotowali plant by measuring the absorbance of p-nitrophenol with UV-Vis spectrophotometry with a wavelength of 400 nm. According to the results of testing the inhibition activity of brotowali ethanol extract at different concentrations showed an IC50 value of 1,663 μg / mL, lower when compared to acarbosa as a comparison that shows an IC50 value of 246 μg / mL. The highest inhibition value of α-glucosidase occurs at the extract dilution concentration of 2000 ppm which is 78.065% and the lowest at the extract dilution concentration of 400 ppm which is 50,098%. Based on the results, it might be drawn to the conclusion that there is an effect of the concentration of brotowali stem extract on inhibition of the enzyme α-glucosidase. If the higher concentration of extract is the lower the value of the injection, causing the higher the value of α-glucosidase inhibitor. If the lower concentration of extract is, the lower the value of inhibitors or inhibitory activity.